Using geoinformation tools for redistricting: Slovenian experiences - Rogelj Boštjan (University of Novi Sad, Department of Geography, Tourism and Hotel Management, 2021)
Electoral districts are an important component of the electoral system, as they have a significant impact on election results. Due to the uneven spatial distribution of electoral support political parties receive, district magnitude and the geography of electoral districts can have a decisive influence on the electoral viability of individual parties and candidates. Districting and redistricting are not a simple bureaucratic process but a politically very sensitive process with outcomes that can have far-reaching political consequences. Geoinformation tools can have a very important role in electoral district planning. In this article we aim to present the key advantages and disadvantages of their use. The presented results are derived from practical experience gained over the course of developing a new system of electoral districts in Slovenia.